Vapor Phase Application of Thymus vulgaris Essential Oil to Control the Biodeteriogenic Fungus Alternaria alternata - Francesca Bosco; Chiara Mollea; Davide Fissore (Applied Sciences)
In the present work, the antimicrobial efficacy of Thymus vulgaris essential oil (EO) was investigated on Alternaria alternata strain BNR; a paper biodeteriogen was used as a model for a contaminated library. The influence of EO volume and diffusion modality, treatment duration, and inoculum age was evaluated in the vapor phase. In Petri dish screening, the influence of different EO volumes (5, 7.5, and 10 μL) on the microbial growth lag phase was investigated, and the growth inhibition period was established. The most effective treatment (10 μL EO) was then scaled up in a glass airtight container of 2650 cm3; a cold diffusion method was applied in order to quickly reach the maximum concentration of active compounds in the vapor phase. These tests demonstrated that EO efficacy is affected by the inoculum age and the contact time, and that the treatment should be performed as early as is feasible. A mycostatic effect was confirmed to be proportional to the utilized EO volume and independent from the treatment method. The information obtained in the present work will be applied to the set-up of an EO treatment in a library characterized by different levels of air contamination.